AERATION OF THE ICE-COVERED WATER POOLS USING THE WAVE FLOW AERATOR - Solomin E.E; Sirotkin E.A.; SolominE.V. (Problems of the Regional Energetics)
This article describes the technical advantages and economic benefits of the ice-covered pool aeration plants consuming power from renewable energy sources. We made a comparative evaluation of the wave flow-aeration method and other methods of pool aeration. We showed the indexes and the characteristics of the wave flow-maker for aeration of ice-covered pools on the territory of Russia. We also made calculations of the economic benefits of aeration plants using the devices converting renewable energy. The project can be scaled and extended to the territory of the CIS, Europe, USA and Canada in the changing climate conditions and the variety of feed reservoirs around the world.